2015
DOI: 10.1111/eip.12255
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective quality of life at first presentation with psychosis

Abstract: We found that both subjective and objective assessments of QOL displayed a degree of clinical utility demonstrated by relationships between clinical factors and both QOL perspectives. Moreover, the lack of association between patient characteristics and QOL shows some potential malleability of QOL outcomes through intervention as there were several clinical factors linked with both subjective and objective QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
12
0
1
Order By: Relevance
“…The stigmatizing attitudes and discrimination experienced by patients with psychotic disorders may negatively impact on their self-esteem and SQoL. Our result that functioning predicted physical SQoL is in keeping with results of earlier studies which showed that impaired global functioning was associated with various aspects of perceived life satisfaction including physical domain in FEP patients (Cotton et al, 2010;Melle et al, 2010;Renwick et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The stigmatizing attitudes and discrimination experienced by patients with psychotic disorders may negatively impact on their self-esteem and SQoL. Our result that functioning predicted physical SQoL is in keeping with results of earlier studies which showed that impaired global functioning was associated with various aspects of perceived life satisfaction including physical domain in FEP patients (Cotton et al, 2010;Melle et al, 2010;Renwick et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Depression has consistently been found to be a robust predictor of SQoL in first-episode populations (Malla et al, 2004;Sim et al, 2004;Law et al, 2005;Melle et al, 2005Melle et al, , 2010Wegener et al, 2005;Cotton et al, 2010;Renwick et al, 2012;Gardsjord et al, 2016). Discrepant findings, however, were observed with respect to the relationships between other clinical variables and SQoL in FEP, with some studies showing premorbid adjustment (Malla et al, 2004;Melle et al, 2005;MacBeth et al, 2015), duration of untreated psychosis (DUP) (Malla et al, 2004;Melle et al, 2005;Gorna et al, 2008), positive symptoms (Gorna et al, 2008;Chee, 2010;Cotton et al, 2010), negative symptoms (Malla et al, 2004;Gorna et al, 2008;Cotton et al, 2010;Thorup et al, 2010) and func tioning (Cotton et al, 2010;Melle et al, 2010;Renwick et al, 2015) as independent factors associated with SQoL, but not others.…”
mentioning
confidence: 99%
“…Aspects of importance to both life satisfaction and quality of life are cognitive, subjective, and objective domains such as psychological well-being, symptoms/outlook, physical health, occupation, social relations, financial status, and the ability to perform activities of daily living. Life satisfaction and quality of life also depend on an individual's adaptation process, perception of their position in life within the context of the culture and the value systems they hold and how these relate to their goals, expectations, standards, and concerns (Arun & Cakiroglu, 2013;Bowen et al, 2015;Campos, Ferreira, Vargas, & Albala, 2014;Diener, Inglehart, & Tay, 2013;Ferna´ndez-Ballesteros et al, 2001;Kim, 2013;Maher, Pincus, Ram, & Conroy, 2015;McNamee & Mendolia, 2014;Mollaoglu, Tuncay, & Fertelli, 2010;Netuveli, Wiggins, Hildon, Montgomery, & Blane, 2006;Oishi, Diener, Lucas, & Suh, 1999;Renwick et al, 2015;Rosengren, Jonasson, Brogardh, & Lexell, 2015;Rouch et al, 2014;Seib et al, 2014;van Leeuwen et al, 2012;WHOQOL Group, 1995;Yamada, Merz, & Kisvetrova, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies about life satisfaction have been conducted among diverse population subgroups. Some studies have measured life satisfaction among people with certain diseases (Bowen et al, 2015;Renwick et al, 2015;Rosengren et al, 2015;van Leeuwen et al, 2012). Others have been conducted in the general population, or among people who are older, in disadvantaged groups (Banjare, Dwivedi, & Pradhan, 2015;Gregersen, Jordansen, & Gerritsen, 2015;Joshanloo, 2016;Kobayashi et al, 2015;Maher et al, 2015;Mollaoglu, Tuncay, & Fertelli, 2010), or in different health-care settings (Wilson, 2012), and countries (Oishi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of inter-observer agreement was established by concurrent assessments between raters in between 5 and 10 cases on SCID-DSM-IV, CDSS, SANS, SAPS, PAS and GAF and agreement between rater's assessments of duration of untreated illness and duration of untreated psychosis were also tested. Concordance coefficients were all within acceptable limits (Shrout and Fleiss, 1979) and are reported elsewhere for this sample (Renwick et al, 2015a). Assessments typically commenced within 48 hours of receipt of referral for assessment and treatment of first-episode psychosis and were conducted sequentially with interviewer assessments first, followed by self-reported assessments upon clinical stabilisation.…”
Section: Methodsmentioning
confidence: 73%